Analysis of the Difference Between Actual Costs and Indonesian Case-Based Group (INA-CBG) Rates for Inpatients with Stroke - Muhammad Kahfiyansyah; Ernani Hadiyati; Umi Muawanah; Yuni Kusuma Arumsari (Global Health Science Group, 2026)
The implementation of the INA-CBGs prospective payment system requires hospitals to ensure that reimbursement tariffs adequately cover actual treatment costs, particularly for stroke, which is a high-cost catastrophic disease. Differences between INA-CBGs tariffs and actual hospital costs may affect hospital financial sustainability. This study aimed to analyse the differences between actual hospital costs and INA-CBGs tariffs in inpatient stroke cases and to identify the effects of length of stay, stroke severity, stroke type, complications, and Cost Recovery Rate (CRR) on these cost differences. This quantitative retrospective study used secondary data from medical records and BPJS claims of 101 inpatient stroke cases selected using total sampling, including all eligible stroke inpatients treated at RSUD dr. Abdul Aziz Singkawang in 2024. Data were analysed using descriptive analysis, t-tests, logistic regression, and CRR calculations. Total actual hospital costs exceeded INA-CBGs reimbursement, resulting in a financial deficit and an overall CRR of 93%. Stroke severity and stroke type significantly influenced cost differences, while length of stay and complications showed indirect effects through increased resource utilisation and prolonged hospitalisation. Severe haemorrhagic stroke cases generated the largest financial losses. Differences between actual costs and INA-CBGs tariffs are influenced by multiple interrelated factors. Severe stroke cases, particularly haemorrhagic stroke, create the greatest financial burden. Tariff evaluation and improved hospital cost management are required to enhance financial efficiency.